2017
DOI: 10.1037/fam0000342
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of coping in a predominantly female sample of caregivers: Contributions to children’s social adjustment in middle childhood.

Abstract: This study applied a short-term longitudinal design to examine whether socialization of coping, observed in real time, predicted social adjustment (i.e., friendship quality and social problems) in middle childhood. Further, this study explored whether socialization of coping contributed to children's social adjustment independent of other aspects of parenting (i.e., positive involvement, autonomy support). Parents' (primarily mothers') coping suggestions were observed while children completed a challenging sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…First, by this age, children have developed an abstract understanding of the concept of race (Hughes, Bigler, & Levy, 2007). Second, prior work has revealed that children in middle childhood are capable of engaging in rich discussions with their parents regarding challenging issues, such as how they cope with stress (Abaied & Stanger, 2017), which suggests that parents and children have the capacity for potentially engaging in challenging discussions about race. Finally, by this age we reasoned that most parents would have had opportunities to discuss race and racism with their child.…”
Section: The Current Studymentioning
confidence: 99%
“…First, by this age, children have developed an abstract understanding of the concept of race (Hughes, Bigler, & Levy, 2007). Second, prior work has revealed that children in middle childhood are capable of engaging in rich discussions with their parents regarding challenging issues, such as how they cope with stress (Abaied & Stanger, 2017), which suggests that parents and children have the capacity for potentially engaging in challenging discussions about race. Finally, by this age we reasoned that most parents would have had opportunities to discuss race and racism with their child.…”
Section: The Current Studymentioning
confidence: 99%
“…Although few studies to date have examined the link between parent SOC and child outcomes, some knowledge is beginning to emerge. For example, two longitudinal investigations have documented that parental engagement coping suggestions were predictive of youth's adaptive stress responses (Abaied & Rudolph, 2011) and social adjustment (Abaied & Stanger, 2017). Similarly, Gaylord‐Harden, Elmore, and Montes de Oca (2013) reported that, in a sample of African American children, maternal socialization of engagement coping was significantly associated with children's use of engagement coping strategies.…”
Section: Parent Socialization Of Emotionmentioning
confidence: 99%
“…Parenting styles and behaviors also remain relatively stable and influence how children communicate with others and navigate social situations (5,6). In the transition from early childhood to middle childhood, children become more independent and interact with others more frequently in a variety of social contexts (7,8). Further, child characteristics such as temperament and emotion regulation can shape patterns of parental responsivity (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%